Evaluation Of The Stress History In A Tailings Dam Raising Stages: A Study Based On Finite Element Method (FEM) Methodology - Ildefonso, Nicole (2024)
Tailings dams are complex geotechnical structures that require a thorough analysis of their stability. The traditional method for assessing stability, the Limit Equilibrium Method (LEM), focuses on calculating the factor of safety (FS), but omits critical aspects such as the stress distribution along the regrowth process. The finite element method (FEM), based on the strength reduction technique (SSR), is an alternative that allows calculating the FS and understanding the real behavior of the slope, by analysing stresses along the different raises stage. In this study, the FEM method was used to simulate the Ancash tailings dam, Peru. The simulation allowed obtaining detailed information on the stress states to which the soil foundation is subjected at each stage of regrowth. The results obtained in terms of displacements and stresses provided a more accurate understanding of the failure mechanism to which the slope may be subjected. It was concluded that the FEM method demonstrated its superiority over the traditional LEM approach, as it provides a more complete and realistic appreciation of the behavior of the slope body at different stages of its development.